PENILAIAN PETANI TERHADAP PERANAN PENYULUH PERTANIAN SEBAGAI AGEN PERUBAHAN DI KECAMATAN DAU KABUPATEN MALANG - Ahmad Zubaidi; Umi Rofiatin (Universitas Tribhuwana Tunggadewi, 2011)
Agricultural extension activity in agricultural development acts as a bridge between farmers and agricultural extension agency in order to inform agriculture innovation to support and to enhance farmer business. The study aimed to determine the farmers' assessment of the role of agricultural extension investigators as an agent of change (facilitators, dynamists/liaisons and motivators) with success level of farmers. This research was carried out for 6 months, in the working area of Agricultural Extension Center of Dau Sub District of Malang Regency. The population sample was farmer groups consisted of 6 groups of beginner, 5 groups of advanced, and 3 groups of middle. The study found that farmers' assessment of the role of agricultural extension as an agent of change as a facilitator and dynamist/liaison, was not good enough and as a motivator had not been optimal yet. The success of farmers in farming in the last growing season is not good even though farmers are already implementing any new innovations with awareness. The relationship between farmers' assessment of the role of agricultural extension as a change agent with the success of farmers in farming was as facilitators, motivator, and dynamist affected the success of farmers in farming on the implementation of changes in farming activities and income of the last planting season